Unique Mode of Lipogenic Activation in Rat Preputial Sebocytes - Dianne Deplewski; Kenan Qin; Nancy Ciletti; Robert L. Rosenfield (Journal of Nutrition and Metabolism)
Lipoprotein delivery of fatty acids and cholesterol is linked with peroxisome proliferator-activated receptor (PPAR) activation in adipocytes and macrophages. We postulated that similar interactions exist in sebaceous epithelial cells (sebocytes) in which PPAR activation induces differentiation. High-density lipoprotein (HDL) and very low-density lipoprotein (VLDL) markedly enhanced sebocyte differentiation above that found with PPAR agonists and were more potent than explicable by their lipid content. The PPARγ antagonist GW5393 reduced sebocyte differentiation to all PPAR isoform agonists, HDL and VLDL, suggesting that the lipoprotein effect on differentiation occurs partially through activation of PPARγ. Furthermore, we found that sebocytes expressed a unique pattern of lipogenic genes. Our results demonstrate that HDL and VLDL are the most potent inducers of sebocyte differentiation tested to date, and these actions are partially inhibited by PPAR antagonists. This suggests that substrates provided by lipoproteins are targeted to sebocytes and affect their own disposition via PPAR activation.